Memes and Anti-Politics. Socio-Semiotic Analysis and the Constitutional Plebiscite in Chile - Cabrera-Medina, J (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2025)
In 2020, Chile held a national plebiscite in which citizens were called to decide whether to draft a new Constitution, choosing between the options "Approve" (Apruebo) and "Reject" (Rechazo). This article analyzes the role of internet memes as semiotic-historical mediating devices in the public debate during this process. Through a narrative and rhetorical approach, it examines memes from both sides of the campaign, selected for their enunciative and ideological constructions. The analysis identifies that memes associated with the Rechazo option tend to reinforce the continuity of a conservative political project, while Apruebo memes operate as verbo-visual texts that critique the neoliberal model, which underpins the current Chilean Constitution. The study concludes by demonstrating how memes, as widely disseminated and popular expressive forms, actively contribute to symbolic and political contestation in contexts of social transformation.